BONE MARROW BIOPSY PICTURE IN A PATIENT WITHMARFANOID HABITUS AND ANOREXIA NERVOSA (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Gelatinous marrow transformation (GMT) is a rare disorder of bone marrow characterized by deposition of extra cellulargelatinous material. There is atrophy of the marrow adipocytes and loss of hematopoietic elements. It is also called asosseous atrophy of the bone marrow. It is not a specific disease but it is seen associated with chronic illness likemalnutrition, anorexia nervosa, HIV infection and administration of cytotoxic drugs. Here, we report a case of gelatinoustransformation of bone marrow in a 17 year old female presented with severe weight loss and anemia